Workplace Experiences of Women With Disability in Sport Organizations - Hanlon, Clare; Taylor, Tracy (Frontiers in Sports and Active Living, 2022)
Women with disability often experience barriers to employment and career progression, most notably in hyper-masculinised industry sectors such as sport. Applying an intersectionality lens and insights from critical disability theory, this research explores the lived experiences of eight women with varying types of disability through their stories of working and volunteering in sport organizations in Victoria (Australia). Analyses of the interviews highlighted the importance that these women attached to their identity as a woman with disability and the intrapersonal and organizational factors that impacted on initial sport workplace attraction and retention. The findings discuss the relationship management strategies adopted to manage these factors in workplace interactions. The interactive effect between disability and gender contributes to building a meaningful understanding of the intersectionality for women with disability in sport organizations.